Metabolites of medicine food homology-derived endophytic fungi and their activities - Jun Zhang; Yihui Zhu; Jinping Si; Lingshang Wu (Current Research in Food Science, 2022)
Medicine food homology (MFH) substances not only provide essential nutrients as food but also have corresponding factors that can prevent and help treat nutritional imbalances, chronic disease, and other related issues. Endophytic fungi associated with plants have potential for use in drug discovery and food therapy. However, the endophytic fungal metabolites from MFH plants and their effects have been overlooked. Therefore, this review focuses on the various biological activities of 108 new metabolites isolated from 53 MFH-derived endophytic fungi. The paper explores the potential nutritional and medicinal value of metabolites of MFH-derived endophytic fungi for food and medical applications. This research is important for the future development of effective, safe, and nontoxic therapeutic nutraceuticals for the prevention and treatment of human diseases.